FUNGICIDE RESIDUES IN APPLE AND CITRUS FRUITS AFTER POST HARVEST TREATMENT (Biological Sciences - PJSIR, 2002)
Thiabendazole and benomyl fungicides after post harvest treatment, were monitored in samples of apples and citrus fruits collected from the main fruit markets of Karachi during the year 1998-99 and 1999-2000. A  total  of  150 samples  (75 samples of each commodity) were screened out of which 82 samples were found to contain either of the t\vo studied  fungicides. Only in 8 samples, Codex exceeded maximum residue  limits  (MRL's)  while  74  samples  contained  residues well  within  permissible limits.